Correspondence and related documents from Anton Klodner to Maria Hummel - Klodner, Anton:::::::::::::::; Hummel, Maria::::::::::::::: (2023)
Correspondence from Anton Klodner to Maria Hummel regarding Karl Hummel's relationship with Chopin. Includes two letters (March 17 and June 7, 1962), a hand-addressed envelope, and a photostat of a portrait engraving of Chopin attributed to Carl Hummel.